Semiconductive microporous hydrogen-bonded organophosphonic acid frameworks - Patrik Tholen (Nature Portfolio, 2020)
Research in hydrogen-bonded organic frameworks (HOFs) has gained interest in recent years due to their facile design and synthesis but no semiconducting HOF has been reported to date. Here the authors report a thermally stable and proton-conductive organic semiconductor based on a porphyrin HOF.